Development of Durian Rind/Polypyrrole Composite and Its Application in Removing of Anionic Dyes - Yan Wang; Zijing Dai; Jiaqi Zha; Wenqing Wei (Adsorption Science & Technology, 2023)
In this study, polypyrrole (PPy) was introduced into durian rind (DR) by in situ polymerization method to prepare durian rind/polypyrrole (DR/PPy) composite. The resulting material was characterized using scanning electron microscope (SEM), transmission electron microscope (TEM), infrared spectroscopy (IRS), and X-ray diffraction (XRD). Then, the removing performance of the DR/PPy material for anionic dyes was explored. The impact of key variables such as the amount of adsorbent, initial dye concentration, pH, adsorption temperature, and contacting time on the adsorption efficiency was examined. The result disclosed that the adsorption efficiency of DR/PPy for methyl orange, sunset yellow, and amaranth was satisfactory. In pH of 7, initial concentration of 100 μg mL-1, and DR/PPy dosage of 1.5 g L-1, the removal efficiency reached 97.31%, 98.48%, and 98.20%, respectively. The adsorptive kinetics and thermodynamic process were analyzed subsequently. The adsorption of anionic dyes on DR/PPy conforms to the pseudo-second-order kinetic and Langmuir isotherm models with maximum adsorption capacity (qm,max) of 193.05, 171.23, and 147.71 mg g-1 for methyl orange, sunset yellow, and amaranth, respectively. Finally, a possible mechanism involved in the adsorption system was put forward. This study implies a reasonable feasibility for the effective utilization of waste to control the pollution.